Perbedaan Tingkat Stres Akademik Siswa Berdasarkan Gaya Belajar Mereka di SMPN 1 Candi Sidoarjo - Navaya Aurelia Kurnia D; Azza Atiqotul Maula A.F; Aqilla Rizki Alvian; Novi Shofariyah; Nadia Lailatuz Zahra; Ayu Wulandari (Departement of Mathematics Education, 2024)
This study aims to identify the differences in academic stress levels among students based on their learning styles at SMPN 1 Candi. The subjects of this research are 8th-grade students from the advanced class. Using a quantitative approach, data was collected through a questionnaire that had undergone validity and normality testing. Before to the F-test, the data was analysed using the homogeneity test to ensure similarity of variance between groups. The F-test was then used to test the proposed hypothesis. The results of the analysis showed a significant difference in academic stress levels between students with different learning styles. The findings provide important insights for educators in adapting learning methods to reduce students' academic stress, especially in advanced classes.